Corporate Sector Vulnerabilities in Ireland - Klein, Nir (IMF Working Papers; Working Paper, 2016)
The paper uses both macro- and micro-level data to assess how has the financial health of the Irish non-financial corporate (NFC) sector changed in the post financial crisis period. The analysis suggests that vulnerabilities have generally declined in recent years, but the NFC sector and especially smaller domestic firms remain vulnerable. A sensitivity analysis indicates that a non-extreme shock, which comprises a decline in profitability and an increase in interest rates, is likely to push many firms into a vulnerable state and that the share of firms with interest cover ratio of lower than one would triple to nearly fifty percent, largely reflecting the deterioration in the financial health of small firms. In such a scenario, the share of risky debt would increase to the level observed during the financial crisis, resulting in a significant increase in new corporate defaults.